2019
DOI: 10.1096/fj.201802427rrr
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from high glucose–treated macrophages activate glomerular mesangial cells via TGF‐β1/Smad3 pathway in vivo and in vitro

Abstract: Diabetes nephropathy (DN) is characterized by abnormal interactions between kidney‐infiltrating macrophages and glomerular mesangial cells. Recently, a novel cell‐cell communication mediated by exosomes has gained attention. Exosomes are membrane‐bound vesicles that contain a variety of molecules such as proteins, lipids, DNA, mRNA, and microRNAs. Exosomes play an important role in the pathogenesis of DN. In this study, we show that high glucose (HG) led to increased excretion of exosomes from macrophages. Mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 32 publications
0
58
0
Order By: Relevance
“…Although macrophage infiltration is linked to the progression of DN, their roles in renal fibrosis during DN are not entirely clear. Interestingly, a recent study found that EVs from macrophages under high glucose condition were taken up by mesangial cells, enhancing the proliferation and excessive ECM secretion in these cells via activating TGF-β1/Smad3 pathways 107 . Mφ-EVs from diabetic conditions were abundant with HuR, an RNA-binding protein that regulates post-transcription, and induce fibrogenesis in fibroblasts 108 .…”
Section: Pathological Roles Of Mφ-evs In Diseasementioning
confidence: 99%
“…Although macrophage infiltration is linked to the progression of DN, their roles in renal fibrosis during DN are not entirely clear. Interestingly, a recent study found that EVs from macrophages under high glucose condition were taken up by mesangial cells, enhancing the proliferation and excessive ECM secretion in these cells via activating TGF-β1/Smad3 pathways 107 . Mφ-EVs from diabetic conditions were abundant with HuR, an RNA-binding protein that regulates post-transcription, and induce fibrogenesis in fibroblasts 108 .…”
Section: Pathological Roles Of Mφ-evs In Diseasementioning
confidence: 99%
“…Internephron crosstalk and interactions between the resident cells play important roles in the development of DKD (Qian et al, 2008;Maezawa et al, 2015;Lv et al, 2019). EVs have emerged as vectors for intercellular communication by transferring information between resident cells and participate in the progression of DKD (Wu et al, 2016(Wu et al, , 2017Wang et al, 2018;Zhu et al, 2019). EVs are membrane-bound vesicles that are continuously secreted by cells and facilitate cellular communication by transferring functional cargo consisting of proteins, lipids, DNA, and RNA (EL Andaloussi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has revealed that EV-mediated intercellular communication plays important roles in the development of DKD. Exosomes derived from high glucose (HG)-treated glomerular endothelial cells (Wu et al, 2016(Wu et al, , 2017, glomerular mesangial cells (Wang et al, 2018), and macrophages (Zhu et al, 2019) transfer injury information to neighboring cells, which accelerates the development of DKD. Structurally, podocytes are located on the outer surface of the glomerular capillary loops adjacent to the proximal tubules.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, exosomes derived from high-glucose-treated glomerular endothelial cells played a crosstalk role to activate epithelial mesenchymal transition (EMT) and fibrotic changes of glomerular mesangial cells and podocytes in DN Wu et al, 2017). High-glucose also enhanced secretion of exosomes from macrophages, which then caused mesangial proliferation and activated inflammatory cascade in the renal tissue (Zhu et al, 2019b). Knockdown of TGF-b1 significantly reduced such effects of exosomes indicating that TGF-b1 serves as an important mediator for interactions or cross talks between macrophages and renal cells (Zhu et al, 2019b).…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…High-glucose also enhanced secretion of exosomes from macrophages, which then caused mesangial proliferation and activated inflammatory cascade in the renal tissue (Zhu et al, 2019b). Knockdown of TGF-b1 significantly reduced such effects of exosomes indicating that TGF-b1 serves as an important mediator for interactions or cross talks between macrophages and renal cells (Zhu et al, 2019b). In addition, advanced glycation end products (AGEs) activated TGF-b-Smad3 signaling pathway and induced secretion of a transcription factor Elf3 through exosomes from the murine podocytes (Sakurai et al, 2019).…”
Section: Chronic Kidney Diseasementioning
confidence: 99%